Thyroid hysterin trabecular adenoma. Case presentation - Miguel Morales Madrigal; Elodia Rivas Alpízar; Javier Martínez Navarro; Ileana Núñez Paredes (Medisur, 2017)
Thyroid hysterin trabecular adenoma is an infrequent neoplasia of the thyroid gland. It is a Tumor of encapsulated follicular origin, relatively small with a benign clinical behavior or of low malignant potential. The case of a 45 year old female patient, is presented, who attended a multidisciplinary thyroid nodule visit at the General University Hospital Dr. Gustavo Aldereguía, from Cienfuegos, with 1 cm in diameter thyroid nodule in the gland left lobe. It underwent a TSH, T4, thyroid ultrasound, fine needle cytology that reported atypia of undetermined significance (according to Bethesda III). Left lobectomy was performed. The histopathological diagnosis was chronic Hashimoto's thyroiditis, on which two neoplastic diseases, macro adenoma and micro follicular thyroid, a hyalinized trabecular thyroid tumor, were inserted, inferior to a non-encapsulated 4x field. The Ki.67 immunohistochemistry technique (MIB.1) was positive. The importance of their diagnosis lies in the fact that they are interpreted by their histological, immunohistochemical and molecular similarities with other entities, such as papillary and medullary thyroid cancer.